Femoral Head and Neck Excision Complicated by Ischiatic Nerve Entrapment in Two Dogs - Jeffery, N. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Two dogs, both Doberman n pinschers, developed ischiatic nerve palsy following femoral head and neck excisions. Each had undergone surgery entailing the incorporation of a muscle flap (in one case deep gluteal, in the other biceps femoris) to reduce bone-on-bone contact after ostectomy. At later exploratory surgery, the ischiatic nerve was found to be entrapped by muscle in the ischiatic fossa, caudal to the greater trochanter. Partial excision of the ischium relieved the compression, allowing rapid recovery of function. The complication of ischiatic nerve entrapment may warrant consideration when contemplating femoral head and neck excision in cases in which the greater trochanter and ischial tuberosity are abnormally close.Ischiatic nerve palsy developed several weeks after femoral head and neck excision in two Dobermann pinschers. Both dogs had undergone surgery involving muscle sling placement. The ischiatic nerve was found to be entrapped in muscle in each case. Resection of portions of the ischium allowed rapid recovery of function.
Keywords: Femoral head and neck excision; ischiatic nerve palsy; ostectomy